2006
DOI: 10.1111/j.1360-0443.2006.01656.x
|View full text |Cite
|
Sign up to set email alerts
|

Theory of mind, humour processing and executive functioning in alcoholism

Abstract: Group comparisons revealed cognitive as well as affective humour processing deficits of alcoholics in comparison with HC. The observed impairments were related to theory of mind and executive functions. The deficits may contribute to interpersonal problems and are thus of relevance to rehabilitation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
71
0
6

Year Published

2007
2007
2020
2020

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 111 publications
(83 citation statements)
references
References 39 publications
6
71
0
6
Order By: Relevance
“…Intact mentalizing abilities are likely to play an important role in humor processing, because the recipient is assumed to adopt the perspectives of the main protagonists to comprehend the correct punchlines. This assumption is consistent with investigations of humor processing in autism, schizophrenia, alcoholism, and normal aging (Corcoran et al, 1997;Uekermann et al, 2006Uekermann et al, , 2007bWinner et al, 1998).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Intact mentalizing abilities are likely to play an important role in humor processing, because the recipient is assumed to adopt the perspectives of the main protagonists to comprehend the correct punchlines. This assumption is consistent with investigations of humor processing in autism, schizophrenia, alcoholism, and normal aging (Corcoran et al, 1997;Uekermann et al, 2006Uekermann et al, , 2007bWinner et al, 1998).…”
Section: Discussionsupporting
confidence: 88%
“…Exclusion criteria were a history of neurological diseases, head trauma, anoxia, psychotic symptoms, stroke, learning disability, and addictive and psychiatric disorders (except depression for the DEP group). Related investigations by the authors (Uekermann et al, 2006(Uekermann et al, , 2007b were separate studies with no overlap of participants.…”
Section: Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Social cognition can be slow and intentional, e.g., the deliberation of a jury in a court of law, but it is also important for successful communication that we are able to process social information quickly and economically in real time social interactions (Apperly, 2012). Increasing evidence shows that social cognition is compromised in those who are alcohol dependent (AD) including the recognition and evaluation of emotional stimuli (Clark et al, 2007;Kornreich et al, 2013;Maurage et al, 2007Maurage et al, , 2008Philippot et al, 1999;Townshend and Duka, 2003); humour processing (Uekermann et al, 2007), understanding how others might feel (Bosco et al, 2014) and tracking the beliefs of others (Maurage et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Uekermann et al (2007) investigated humour processing in adults with AD and reasoned that one needs to understand another"s mind in order to "get" the joke. In a joke completion task, they found that humour processing was impaired in AD participants.…”
Section: Introductionmentioning
confidence: 99%